2004
DOI: 10.1073/pnas.0405048101
|View full text |Cite
|
Sign up to set email alerts
|

Ringwoodite lamellae in olivine: Clues to olivine–ringwoodite phase transition mechanisms in shocked meteorites and subducting slabs

Abstract: The first natural occurrence of ringwoodite lamellae was found in the olivine grains inside and in areas adjacent to the shock veins of a chondritic meteorite, and these lamellae show distinct growth mechanism. Inside the veins where pressure and temperature were higher than elsewhere, ringwoodite lamellae formed parallel to the {101} planes of olivine, whereas outside they lie parallel to the (100) plane of olivine. The lamellae replaced the host olivine from a few percent to complete. Formation of these lame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 27 publications
6
50
1
2
Order By: Relevance
“…This indicates the transformation begin from the rims of the clasts. This hypothesis can be supported by the investigations of ringwoodite lamellae in olivine in the shock veins of Sixiangkou chondrite [31] and Yamato 791384 chondrite [39]. Chen et al [31] reported that ringwoodite lamellae in the rim of olivine grains are thicker and have higher densities than in their interior.…”
Section: Olivine-ringwoodite Transformation Processsupporting
confidence: 68%
See 1 more Smart Citation
“…This indicates the transformation begin from the rims of the clasts. This hypothesis can be supported by the investigations of ringwoodite lamellae in olivine in the shock veins of Sixiangkou chondrite [31] and Yamato 791384 chondrite [39]. Chen et al [31] reported that ringwoodite lamellae in the rim of olivine grains are thicker and have higher densities than in their interior.…”
Section: Olivine-ringwoodite Transformation Processsupporting
confidence: 68%
“…Natural ringwoodite was first discovered in the Tenham L6 chondrite [21], and so far it was identified only in shocked meteorites, such as ordinary chondrites, carbonaceous chondrites, lunar meteorites, and Martian meteorites [6,8,[22][23][24][25][26][27][28], except one terrestrial sample, as an inclusion in a tiny diamond crystal [29]. Ringwoodites in meteorites are generally found within or directly adjacent to shock-melt veins and pockets, where it mainly occurs as fine grained polycrystalline aggregates [27,30] and lamellar [22,31]. Phase transformation is a complex process.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum shock pressure and temperature, as constrained by the former perovskite, are 25-40 GPa and c2,000 1C, respectively [14][15][16][17] . Other occurrences of high-P minerals indicate shock pressures of 13-25 GPa and temperatures of 1,700-2,600 1C in melt pockets [17][18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Other occurrences of high-P minerals indicate shock pressures of 13-25 GPa and temperatures of 1,700-2,600 1C in melt pockets [17][18][19][20][21][22][23][24][25] . Furthermore, the absence of lingunite decomposition products (calcium ferrite-type NaAlSiO 4 þ stishovite) suggests a P-T upper limit of 24 GPa at B1,800-2,000 1C (refs 26,27).…”
Section: Discussionmentioning
confidence: 99%
“…A partially transformed texture was also found in some olivine grains which were located close to the vein edge. In some cases ringwoodites appeared as lamellae, as it is shown in optical and reflected light images (Figs 4 and 5); this was first published by Chen et al (2004). The lamellae system shows at least three different orientations in a given section, which might have corresponded to rational crystallographic planes of olivine.…”
Section: Microstructures Of Ringwoodite In Nwa 5011mentioning
confidence: 83%